Choice Defines QALYs: A US Valuation of the EQ-5D-5L. Issue 6 (June 2018) - Craig, Benjamin M.; Rand, Kim
Abstract : Background: The 5-level version of the EQ-5D (EQ-5D-5L) was introduced as an improvement on the original 3-level version (EQ-5D-3L). To date, 6 country-specific value sets have been published for EQ-5D-5L and 9 US value sets have been published for other instruments. Our aims were to (1) produce EQ-5D-5L values on a quality-adjusted life year (QALY) scale from the perspective of US adults and (2) compare them with US EQ-5D-3L values and the other country-specific EQ-5D-5L values. Methods: In 2016, 8222 US respondents from all 50 states and Washington, DC completed an online survey including a discrete choice experiment with 20 paired comparisons. Each comparison asked respondents, "Which do you prefer?" regarding a pair of alternatives described using EQ-5D-5L and lifespan attributes. On the basis of more than 50 choices on each of the 3160 pairs, we estimated EQ-5D-5L values on a QALY scale and compared them with the US EQ-5D-3L values and the other country-specific EQ-5D-5L values. Results: Ranging from −0.287 (55555) to 0.992 (11121) on a QALY scale, the estimated EQ-5D-5L values were similar to the US EQ-5D-3L values. Compared with the US EQ-5D-3L values, the values exhibited greater sensitivity and specificity and higher correlation with the EQ-5D-5L values of other countries, particularly England. Conclusions: Like previous US valuation studies, this study produced nationally representative EQ-5D-5L values on a QALY scale. The results further demonstrate the advantages of the EQ-5D-5L over its 3-level predecessor as a preference-based summary measure of health-related quality of life from the perspective of US adults. Abstract : Supplemental Digital Content is available in the text.